The Enforcement of Progressive Law in Indonesia: In the Treatment of Terrorist Convict - Anwar, Umar; Priyatmono, Budi (Sekolah Tinggi Ilmu Kepolisian, 2025)
The treatment of terrorist inmates at the Nusakambangan Correctional Institution has not been running optimally. The impact is that there are still many terrorist prisoners who do not recognize Pancasila, the unitary state of the Republic of Indonesia and are unable to reduce their criminal risk. The purpose of his research is to explore the application of Progressive Law in improving the treatment of terrorist inmates in the Nusakambangan Super Maximum Security Correctional Institution (SMAX) in Indonesia. The research method with a Socio-legal approach, by conducting direct research on terrorist inmates in the Nusakambangan SMAX prison, data collection techniques conducted in-depth interviews and observation of the lives of inmates in the Nusakambangan correctional institution. The results of the analysis show that the implementation of personality treatment for terrorist inmates in SMAX Prison is not carried out in a well-directed manner in accordance with the goals of correction. Coaching is only carried out based on the concept that exists in correctional institution officers, community supervisors, at any time presented by Densus 88 Polri and the National Agency for Countering Terrorism. So that the coaching carried out with a progressive legal approach has not been optimally implemented because it emphasizes strict security based on existing regulations without paying attention to the maximum appropriate guidance for terrorist prisoners. It is hoped that the state can pay attention to the pattern of fostering legal awareness by involving all related elements to the maximum so that it can increase the awareness of the law of the nation and the state for terrorist prisoners.